Adverse effects of political sanctions on the health care system in Iran - Roxanne L Massoumi; Sumana Koduri (Edinburgh University Global Health Society, 2015)
Economic sanctions are widely believed to be a peaceful alternative to war: sparing harm to the average citizens of a nation while putting firm pressure on their government to elicit a change. This generalization does not take into account the often overlooked impact sanctions can have on a nation's healthcare system and thus indirectly on its citizens. Iran's healthcare system has been indirectly affected by the U.S. sanctions in terms of availability and affordability of medicine, as well as their ability to contribute to the global research community.